2013
DOI: 10.1007/s00280-013-2304-9
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor signaling regulates cisplatin-induced mechanical allodynia in mice

Abstract: Purpose Cisplatin treated mice develop a persistent pain state and a condition wherein otherwise innocuous tactile stimuli evoke pain behavior, e.g. tactile allodynia. The allodynia is associated with an up-regulation of Activation Transcription Factor 3 (ATF3) in the dorsal root ganglia (DRG), a factor, which is activated by Toll-like receptors (TLR). Accordingly, we sought to examine the role of the TLR signaling cascade on allodynia, weight and changes in DRG ATF3 in cisplatin-treated mice. Methods Cispla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 40 publications
4
58
0
Order By: Relevance
“…AIBP on the expression of several pain states known to be associated with neuraxial TLR4 signaling. Tlr4 gene knockout or mutant mice are fully protected from tactile allodynia in the models of facilitated pain tested below (Cao et al, 2009; Park et al, 2014; Saito et al, 2010; Sorge et al, 2011; Stokes et al, 2013a; Stokes et al, 2013b; Woller et al, 2015). Accordingly, we addressed the effects of i.t.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AIBP on the expression of several pain states known to be associated with neuraxial TLR4 signaling. Tlr4 gene knockout or mutant mice are fully protected from tactile allodynia in the models of facilitated pain tested below (Cao et al, 2009; Park et al, 2014; Saito et al, 2010; Sorge et al, 2011; Stokes et al, 2013a; Stokes et al, 2013b; Woller et al, 2015). Accordingly, we addressed the effects of i.t.…”
Section: Resultsmentioning
confidence: 99%
“…To address the functional impact of AIBP on TLR4 signaling, we took note of the evolving understanding of the role played by neuraxial TLR4 in regulating the development of facilitated pain states generated by tissue and nerve injury (Park et al, 2014; Saito et al, 2010; Sorge et al, 2011; Stokes et al, 2013b; Woller et al, 2015). TLR4 deficiency in mice prevents the tactile allodynia otherwise evolving over time after afferent activation, as observed with intraplantar formalin (Woller et al, 2016) or as seen with the chemotherapeutic agent cisplatin (Park et al, 2014; Woller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hill et al (55) reported that just skin incision, without substantial nerve damage, causes an increase of ATF3, galanin, and other injury markers; ATF3 is found in 2.9% of DRG neurons after skin incision vs. 0.07% in controls. Up-regulation of such markers has been described in multiple conditions, including osteoarthritis, chemotherapy, and other noninvasive procedures, although osteoarthritis and chemotherapy are likely to damage nerves (56)(57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of macrophages in the DRG and antigen-presenting Langerhans cells in the skin has also been observed following the administration of paclitaxel. 115,260 Furthermore, modulation of known inflammatory signaling pathways, such as NFκB 141 and Toll-like receptor (TLR) signaling 261,262 attenuate the behavioral effects of chemotherapy administration in preclinical models. Indeed, paclitaxel administration to rats enhances the expression of the TLR4 in the DRG and spinal cord.…”
Section: Inflammationmentioning
confidence: 99%